Evaluation of perceived collaborative behaviour amongst stakeholders and clinicians of a continuing education programme in arthritis care. Issue 5 (17th May 2013) - Lundon, Katie; Kennedy, Carol; Rozmovits, Linda; Sinclair, Lynne; Shupak, Rachel; Warmington, Kelly; Passalent, Laura; Brooks, Sydney; Schneider, Rayfel; Soever, Leslie
Abstract: Successful implementation of new extended practice roles which transcend conventional boundaries of practice entails strong collaboration with other healthcare providers. This study describes interprofessional collaborative behaviour perceived by advanced clinician practitioner in arthritis care (ACPAC) graduates at 1 year beyond training, and relevant stakeholders, across urban, community and remote clinical settings in Canada. A mixed-method approach involved a quantitative (survey) and qualitative (focus group/interview) evaluation issued across a 4-month period. ACPAC graduates work across heterogeneous settings and are on teams of diverse size and composition. Seventy per cent perceived their team as actively working in an interprofessional care model. Mean scores on the Bruyère Clinical Team Self-Assessment on Interprofessional Practice subjective subscales were high (range: 3.66–4.26, scale: 1–5 = better perception of team's interprofessional practice), whereas the objective scale was lower (mean: 4.6, scale: 0–9 = more interprofessional team practices). Data from focus groups (ACPAC graduates) and interviews (stakeholders) provided further illumination of these results at individual, group and system levels. Issues relating to ACPAC graduate role recognition, as well as their deployment, integration and institutional support, including access to medical directives, limitation of scope of practice, remuneration conflicts and tenuous funding arrangements were barriers perceived to affect role implementation and interprofessional working. This study offers the opportunity to reflect on newly introduced roles for health professionals with expectations of collaboration that will challenge traditional healthcare delivery.